Stem Cell-Based Therapeutic Approaches to Restore Sensorineural Hearing Loss in Mammals - Muhammad Waqas; Iram Us-Salam; Zainab Bibi; Yunfeng Wang; He Li; Zhongshou Zhu; Shuangba He (Neural Plasticity)
The hair cells that reside in the cochlear sensory epithelium are the fundamental sensory structures responsible for understanding the mechanical sound waves evoked in the environment. The intense damage to these sensory structures may result in permanent hearing loss. The present strategies to rehabilitate the hearing function include either hearing aids or cochlear implants that may recover the hearing capability of deaf patients to a limited extent. Therefore, much attention has been paid on developing regenerative therapies to regenerate/replace the lost hair cells to treat the damaged cochlear sensory epithelium. The stem cell therapy is a promising approach to develop the functional hair cells and neuronal cells from endogenous and exogenous stem cell pool to recover hearing loss. In this review, we specifically discuss the potential of different kinds of stem cells that hold the potential to restore sensorineural hearing loss in mammals and comprehensively explain the current therapeutic applications of stem cells in both the human and mouse inner ear to regenerate/replace the lost hair cells and spiral ganglion neurons.